SAMHD1 as the Potential Link Between SARS-CoV-2 Infection and Neurological Complications - Khan, Aiza; Sergi, Consolato (Frontiers in Neurology, 2020)
The recent pandemic of coronavirus infectious illness 2019 (COVID19) triggered by SARS-CoV-2 has rapidly spread around the globe, generating in severe events an acute, highly lethal pneumonia and death. In the past two hitherto similar CoVs, the severe acute respiratory syndrome CoV (SARS-CoV-1) and Middle East respiratory syndrome CoV (MERS-CoV) also gained universal attention as they produced clinical symptoms similar to those of SARS-CoV-2 utilizing angiotensin-converting enzyme 2 (ACE2) receptor and dipeptidyl peptidase 4 (DPP4) to go into the cells. COVID-19 may also present with overtly neurological symptoms. The proper understanding of the expression and dissemination of ACE2 in central and peripheral nerve systems is crucial to understand better the neurological morbidity caused by COVID-19. Using the STRING bioinformatic tool and references through text mining tools associated to Coronaviruses, we identified SAMHD1 as the probable link to neurological symptoms. Paralleled to the response to influenza A virus and, specifically, respiratory syncytial virus, SARS-CoV-2 evokes a response that needs robust induction of a subclass of cytokines, including the Type I and, obviously, Type III interferons as well as a few chemokines. We correlate ACE2 to the pathogenesis and neurologic complications of COVID-19 and found that SAMHD1 links to NF-κB pathway. No correlation was found with other molecules associated with Coronavirus infection, including ADAR, BST2, IRF3, IFITM3, ISG15, MX1, MX2, RNASEL, RSAD2, and VPRBP. We suggest that SAMHD1 is the molecule that may be behind the mechanisms of the neurological complications associated with COVID-19.